Multispecies spatial dynamics under different protection levels: an evaluation of the effects and optimal design of the Luiz Saldanha Marine Park - Abecasis, David Maria Aguiar (2015)
Doutoramento em Ciências do Mar, Faculdade de Ciências e Tecnologia, Universidade do Algarve, 2013